European quality clearance of new microbiological diagnostics. (29th October 2012) - Ieven, M.; Finch, R.; van Belkum, A.
<x xml:space="preserve">Abstract</x> Clin Microbiol Infect Abstract Laboratory‐based diagnosis of infectious diseases is evolving quickly. New technologies and new tests are frequently commercialized, and although guidelines for their proper clinical validation do exist, these are often at the national or regional level. Therefore, the guidelines remain open to interpretation, and are not always applied properly. One of the main questions is how a high level of test quality can be maintained by European legislation. How can product quality be reliably and independently assessed and how can the penetration of sub‐standard assays in the European market be managed and hopefully prevented? We here propose that local initiatives, including external quality assessment, public health initiatives, and close multidisciplinary collaborations between manufacturers and academic research institutes, may accelerate decision‐making. Vigilance in test quality assessment and legal simplification are important key concepts warranting selective use of those diagnostic tests that comply with the highest quality standards.